Assessing preregistration nursing students' clinical competence: A systematic review of objective measures. Issue 2 (12th April 2013) - Cant, Robyn; McKenna, Lisa; Cooper, Simon
<x xml:space="preserve">Abstract</x> Nursing students are required to develop clinical knowledge, skills and attitudes for professional practice. However, objectivity and parity of students' clinical assessments has been questioned. In the last decade, more objective techniques have been developed, with increased use of Objective Structured Clinical Examinations. We reviewed objective clinical assessment measures used in preregistration nursing courses to determine utilization and the validity and reliability of assessment techniques. A systematic search was made of quantitative research publications between 2000 and May 2011, identifying 16 studies that were subsequently reviewed. The validity and reliability of studies varied, with six studies judged as high quality, using various methodologies. This paper describes methods of instrument development and reports on their application in preregistration nursing programs.